Engineering Inclusion in Indian Workplaces: A Mumbai-Based Study on Sign Language and Assistive Tech Integration - Souumya Kothari (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
In the changing dynamics of workplace diversity, there is a growing movement from just representation to creating real inclusion, particularly for people with disabilities. The study examines the extent of awareness and use of sign language and assistive technologies in Mumbai-based organizations and how they affect employee productivity and job satisfaction. The study employs a mixed-method design, incorporating both quantitative and qualitative data to provide an in-depth understanding of inclusive communication practices. A stratified purposive sampling design was employed to reflect a range of diverse perspectives by organizational types and disability categories. Statistical methods including Pearson correlation and regression were applied to analyze data through SPSS 26. Results confirm a strong positive correlation between the organizational type and the utilization of inclusive tools, which implies that structural and cultural influences within the organization affect the level of accessibility. Moreover, inclusive communication practices were found to significantly and statistically impact employee productivity as well as job satisfaction. These findings emphasize the strategic value of transcending performative diversity initiatives in embracing practical, inclusive interventions that facilitate participation by everyone. The research points to the indispensable role of leadership and organizational engagement in fostering inclusion and provides insights into how these practices can translate into better workplace outcomes. Although the study has some rich contributions, its geographic limitation and use of self-reported data necessitate subsequent studies in more diverse and large contexts.